Assessment of Changes in Executive Functions and Attention of Cadets as a Result of Military Parachute Jumping - Dariusz Jamro; Marek Kociuba; Maciej Lachowicz; Pawel Korytko; Grzegorz Zurek (Brain Sciences)
Objectives: This study analyzed the effects of parachute jump stress on the executive functions and attention of cadets. Executive functions, which includes processes such as attentional control and cognitive flexibility, are crucial for soldiers, especially in situations requiring rapid decision-making. Parachute jumping, as an intense stressor, mobilizes cognitive resources, which can lead to short-term improvements in executive functions. Methods: A total of 64 cadets divided into control (N = 32) and experimental (N = 32) groups participated in the study. The experimental group performed a parachute jump and then took the Color Trails Test, assessed both before and after the jump. Results: The results showed significant improvements in executive functions, in particular, sustained and alternating attention, sequential information processing, and monitoring one’s own behavior, suggesting a positive effect of stress on selected executive functions. Conclusions: The results indicate that intense, short-term stress can positively affect executive functions, although this effect may depend on the type of task and the participants’ experience of exposure to intense stressful stimuli. The study makes an important contribution to the design of future military training, considering the importance of mobilizing cognitive resources in response to short-term stress.